Preparation and Training Needs of Teachers to Teach Entrepreneurship in Vocational Programmes - Lope Pihie, Zaidatol Akmaliah (Universiti Putra Malaysia Press, 1993)
The purpose of the study was to identify teachers' perceptions regarding the qualifications and training needs of vocational teachers in relation to teaching entrepreneurial competencies. Subjects were randomly selected from a list of vocational teachers' names and addresses in the State of Illinois, U.S.A., and data were collected by questionnaire. The findings illustrate that educators believe that having a degree in education and having business management knowledge are important qualifications for teaching entrepreneurship. Training is most needed for teaching competencies which are more specialized and require a high level of knowledge. The findings also indicate that teachers who have more business knowledge and more business experience are more likely to emphasize entrepreneurial competencies in their instruction. This study suggests a teacher preparation model that can improve the quality of teacher training in entrepreneurship. Future entrepreneurship teachers should be thoroughly prepared through an effective teacher training curriculum.